2000
DOI: 10.1034/j.1600-0560.2000.027007338.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of ornithine decarboxylase in skin tumors

Abstract: These results support the conclusion that the intensity and the incidence of positive immunohistochemical staining for ODC correlate with the degree of cellular differentiation, and furthermore, that heterogenous distribution of ODC staining may be associated with heterogeneity of tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
(25 reference statements)
2
11
0
Order By: Relevance
“…Enhanced epidermal cyst formation has also been observed in the skin of some NBCCS patients (52,53). While ODC expression has not been assessed in the multiple BCCs in NBCCS patients (27), it seems highly likely that these lesions will manifest increased expression of this enzyme. A corollary to this hypothesis is that the epithelial lining of odontogenic keratinocysts in NBCCS patients has enhanced growth potential demonstrated by high expression of known proliferation markers such as PCNA and Ki67 (53)(54)(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Enhanced epidermal cyst formation has also been observed in the skin of some NBCCS patients (52,53). While ODC expression has not been assessed in the multiple BCCs in NBCCS patients (27), it seems highly likely that these lesions will manifest increased expression of this enzyme. A corollary to this hypothesis is that the epithelial lining of odontogenic keratinocysts in NBCCS patients has enhanced growth potential demonstrated by high expression of known proliferation markers such as PCNA and Ki67 (53)(54)(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 98%
“…UVB rapidly induces papillomas and SCCs in transgenic mice with keratin 5 promoter-driven overexpression of ODC compared with non-transgenic littermates (25). It is unclear whether these mechanisms of tumor promotion that are pertinent to induction of SCCs are relevant to BCCs, although, as mentioned earlier, ODC activity is increased in BCCs (20,26,27). Cellular polyamine content is tightly regulated by various mechanisms, including transcriptional, translational, and posttranslational regulation of the enzymes responsible for polyamine synthesis and catabolism as well as a highly inducible polyamine-transport system (18,28).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…O'Brien et al (39) showed that in transgenic mice, overexpression of ODC in skin was associated with elevated tissue polyamines, particularly putrescine and the development and maintenance of the neoplastic phenotype (40). ODC has also been found to be elevated in SCC compared with normal skin (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…The skin specimens from acne patients, from control subjects and from organ culture were fixed in periodate‐lysine‐2% paraformaldehyde solution for 6 h at 4°C, rinsed in 0.01 M phosphate buffered saline (PBS) (pH 7.6) containing a series of graded concentrations of sucrose, and then embedded in OCT compound (Miles Scientific, Elkhart, IN, USA). Eight μm sections were cut using a cryostat, mounted on poly‐L‐lysine coated glass slides, and air dried at room temperature for 3 h. Immunohistochemistry was performed on these sections using an enhanced labeled polymer system conjugated to anti‐mouse and anti‐rabbit immunoglobulins (Dako, Kyoto, Japan), as previously described (20). After the specimens were rinsed with PBS, they were treated with 0.3% hydrogen peroxide in methanol for 10 min to inactivate endogenous peroxidase.…”
Section: Methodsmentioning
confidence: 99%